Effects of combination therapy of antithrombin and thrombomodulin for sepsis-associated disseminated intravascular coagulation: a systematic review and meta-analysis - Totoki, Takaaki; Makino, Yuto; Yamakawa, Kazuma; Koami, Hiroyuki; Wada, Takeshi; Ito, Takashi; Iba, Toshiaki (Thrombosis journal, 2024)
Background Disseminated intravascular coagulation (DIC) syndrome is a highly lethal condition characterized by the complication of multiple organ damage. Although the effects of combined antithrombin (AT) and recombinant thrombomodulin (rTM) on DIC syndrome have previously been examined, the results are inconsistent and inconclusive. Therefore, we conducted a systematic review on the combined administration of AT and rTM for the treatment of septic DIC to investigate the superiority of the combination therapy over either AT or rTM monotherapy using a random-effects analysis model. Method We searched electronic databases, including Medline, Cochrane Central Register of Controlled Trials, Scopus, and Igaku-Chuo Zasshi (ICHU-SHI) Japanese Central Review of Medicine Web from inception to January 2022. Studies assessing the efficacy of combined AT and rTM were included. The primary outcome was all-cause mortality, and the secondary outcome was occurrence of serious bleeding complications compared to monotherapy. We presented the pooled odds ratio (OR) or hazard ratio (HR) with 95% confidence intervals (CI) depending on reporting results in each primary study. Results We analyzed seven enrolled clinical trials, all of which were observational studies. Combination therapy had a non-significant favorable association with lower 28-day mortality compared to monotherapy (HR 0.67 [0.43–1.05], OR 0.73 [0.45–1.18]). The I 2 values were 60% and 72%, respectively, suggesting high heterogeneity. As a secondary outcome, bleeding complications were similar between the two groups (pooled OR 1.11 [0.55–2.23], I 2 value 55%). Conclusions Although the findings in this analysis could not confirm a statistically significant effect of AT and rTM combination therapy for septic DIC, it showed a promising effect in terms of improving mortality. The incidence of bleeding was low and clinically feasible. Further research is warranted to draw more conclusive results. Trial registration This study was registered in the University Hospital Medical Information Network (UMIN) Clinical Trials Registry (UMIN ID: 000049820).